Analisis Kepentingan Nasional Bangladesh dalam Kebijakan Penghentian Penerimaan Pengungsi Rohingya - Arifin, Mizan; Wahyudi, Fendy Eko (Journal of International Relations, 2021)
Bangladesh, a neighboring country of Myanmar, has received the direct impact of the Rohingya refugee crisis which has not ended, especially in the economic and security aspects. This study aims to explain the process as well as the background of the Government of Bangladesh in issuing a policy to stop the admission of Rohingya refugees starting March 2019. This research is a qualitative study that uses a rational choice framework and the concept of national interest. Based on the analysis conducted, it is known that the Government of Bangladesh issued this policy in order to protect national interests in the economic and security sector, and this policy is the most rational choice based on cost-benefit considerations compared to other policies.